Biosurfactants: Potential Agents for Controlling Cellular Communication, Motility, and Antagonism - Sharma, Jyoti; Sundar, Durai; Srivastava, Preeti (Frontiers in Molecular Biosciences, 2021)
Biosurfactants are surface-active molecules produced from microorganisms either on the cell surface or secreted extracellularly. They form a thin film on the surface of microorganisms and help in their detachment or attachment to other cell surfaces. They are involved in regulating motility of bacteria and quorum sensing. Here, we describe the various types of biosurfactants produced by microorganisms and their role in controlling motility, antagonism, virulence and cellular communication.